PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH - Khairuman, Miftah; Noermijati, Noermijati (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
In winning the competition to win the hearts of bank customers, they must design a strategy regarding service quality. Banks as a sector of financial services, its performance will depend on whether the overall service is good or bad for its customers. The better the service from a bank, the relatively easier it will be to gain the trust of customers to deposit funds or apply for a loan at that bank. The purpose of this study is to identify the effects of tangibles, empathy, reliability, responsiveness, and assurance on customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Madiun. This study is considered as explanatory research since it explains the causal relationship between variables through hypothesis testing. The samples are 215 saving service customers of the bank, the number of which were set using Slovin formula. The data was analyzed using descriptive statistics and multiple linear regression, performed in SPSS version 26. This study finds that tangibles, empathy, reliability, responsiveness, and assurance significantly influence the satisfaction of the saving service customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Madiun.